Validity of judo-specific tests to assess neuromuscular performance of judo athletes - Kons, R. L.; Da Silva Junior, J. N.; Follmer, B.; Guarise Katcipis, L. F.; Almansba, R.; Detanico, D. (Sports Biomechanics, 2021)
Uchi-komi Fitness Test (UFT) is a specific judo test that evaluates physiological fitness of judo athletes in similar conditions to judo matches. Neuromuscular parameters obtained by generic and judo-specific tests would aid to get more information about its criterion validity. This study aimed to analyse the relationship between UFT and shoulder external (PTEX) and internal (PTINT) rotation torque, handgrip strength (HGS) and vertical jumps (VJs) performance. The relationship between UFT and Judogi grip strength test (JGST) was also investigated. Eighteen male judo athletes participated in this study. Athletes performed neuromuscular tests (VJ, PTEX, PTINT and HGS) and judo-specific tests (JGST and UFT). Pearson`s correlation was used with the level set at p < 0.05. Significant correlation was found between UFT and all VJ variables (r = 0.50-0.72, p < 0.004), UFT a + b (two first series of UFT) and PTEX (r = 0.49, p = 0.033), UFT and PTINT (r = 0.47, p = 0.044). Also, UFT was correlated to JGST (r = 0.50-0.72, p < 0.044, respectively). We conclude that muscle power of lower limbs, PTEX and PTINT was related to UFT. Strength-endurance in the upper limbs (JGST) was also related to the UFT performance.